2003
DOI: 10.1183/09031936.03.00057003
|View full text |Cite
|
Sign up to set email alerts
|

New concepts of the pathogenesis of cystic fibrosis lung disease

Abstract: Although there has been impressive progress in the elucidation of the genetic and molecular basis of cystic fibrosis (CF), the pathogenesis of CF lung disease remains obscure. The elucidation of the pathogenesis of CF lung disease requires both a full description of normal innate airway defence and how absent function of the cystic fibrosis transmembrane regulator protein (CFTR) adversely perturbs this activity.Recent data have linked the abnormal ion transport properties of CF airway epithelia to depleted air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
410
2
15

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(438 citation statements)
references
References 107 publications
11
410
2
15
Order By: Relevance
“…This is a necessary but not sufficient component of the pathogenesis of P. aeruginosa in CF that is well documented and supported by the work of Boucher and colleagues [13]. But this abnormal physiology does not provide an explanation for why P. aeruginosa is so clearly the predominant pathogen in CF, as other pathogens could probably take advantage of this niche to cause lung infection.…”
Section: Pseudomonas Aeruginosa In Cystic Fibrosismentioning
confidence: 98%
See 1 more Smart Citation
“…This is a necessary but not sufficient component of the pathogenesis of P. aeruginosa in CF that is well documented and supported by the work of Boucher and colleagues [13]. But this abnormal physiology does not provide an explanation for why P. aeruginosa is so clearly the predominant pathogen in CF, as other pathogens could probably take advantage of this niche to cause lung infection.…”
Section: Pseudomonas Aeruginosa In Cystic Fibrosismentioning
confidence: 98%
“…The alterations in pH, ion concentration and ASL hydration are all potential factors contributing to P. aeruginosa infecting a high proportion of CF patients. Although it has been proposed that there is an elevated salt concentration in CF ASL that inhibits the activities of antibacterial substances, including lysozyme, lactoferrin and β-defensins [26], most studies [13] have not confirmed the early observation. Better established are findings pointing to a high viscosity of the ASL that then hinders the normal beat of the ciliated airway epithelial cells, which in turn compromises mechanical clearance of P. aeruginosa from the airway, allowing for retention of organisms within the airway lumen [7] (Box 1).…”
mentioning
confidence: 99%
“…12 As an alternative, we and others have begun to investigate the use of endogenous, cell-type specific promoters to target the expression of CFTR to the airway epithelium where the CFTR protein is a critical regulator of the volume of airway surface liquid. 13 For example, Hu and co-workers 14 have developed an expression cassette using the promoter from the keratin 18 gene. Previously, we have demonstrated that a small fragment of the human FOXJ1 promoter is sufficient to target the expression of a reporter (enhanced green fluorescent protein (EGFP)) to the ciliated cells of the respiratory tract in a transgenic mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic obstructive pulmonary diseases (COPDs) are essentially observed in cigarette smokers and share many clinical features with CF (cystic fibrosis) (2), a disease caused by mutations of the cAMP-activated cystic fibrosis transmembrane conductance regulator (CFTR) Cl − channel. In COPD and patients with cystic fibrosis (CF), the lack of functional CFTR in the airways results in altered ion transport at the apical membrane, mucus dehydration and hyperviscosity, reduced mucus transport, the inability to prevent bacterial infections, and the progressive decline of lung function (2)(3)(4). In addition, cigarette smoke decreases cAMPdependent Cl − secretion in vivo (5,6) and in vitro (7), a process possibly related to smoke oxidants (8).…”
mentioning
confidence: 99%